2018
DOI: 10.1007/s00222-018-0806-0
|View full text |Cite
|
Sign up to set email alerts
|

Singular foliations with trivial canonical class

Abstract: This paper describes the structure of singular codimension one foliations with numerically trivial canonical bundle on complex projective manifolds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 52 publications
1
52
0
Order By: Relevance
“…Techniques from algebraic geometry have been extremely useful in the study of singular holomorphic foliations, see for instance [2,5,20,24,26,33,37,39]. In particular, Jouanolou classified codimension one foliations on P 3 of degrees 0 and 1 in his monograph [33]; Cerveau and Lins Neto showed in [16] that there exist six irreducible components of foliations of degree 2 on projective spaces; and Polishchuk, motivated by the study of holomorphic Poisson structures, also found in [44] a classification of foliations of degree 2 on P 3 under certain hypotheses on the singular set of the foliations.…”
Section: Introductionmentioning
confidence: 99%
“…Techniques from algebraic geometry have been extremely useful in the study of singular holomorphic foliations, see for instance [2,5,20,24,26,33,37,39]. In particular, Jouanolou classified codimension one foliations on P 3 of degrees 0 and 1 in his monograph [33]; Cerveau and Lins Neto showed in [16] that there exist six irreducible components of foliations of degree 2 on projective spaces; and Polishchuk, motivated by the study of holomorphic Poisson structures, also found in [44] a classification of foliations of degree 2 on P 3 under certain hypotheses on the singular set of the foliations.…”
Section: Introductionmentioning
confidence: 99%
“…It seems possible that the stability of F is enough to imply the algebraicity of leaves (cf. also [Tou08,LPT11,LPT13,PT13] for classification results of foliations with c 1 (F ) = 0).…”
mentioning
confidence: 99%
“…Let G be a foliation with numerically trivial canonical class on a complex projective manifold, and assume that G has a compact leaf. Then Theorem 5.6 in [LPT18] asserts that G is regular and that there exists a foliation on X transverse to G at any point in X. In this section, we extend this result to our setting (see also [DPS01, Proposition 2.7.1] and [Dru18a, Corollary 7.22]).…”
Section: A Criterion For Regularitymentioning
confidence: 71%